Analysis of Knowledge and Understanding of Regarding Waste Management in the Aie Dingin Landfill Area in Balai Gadang Koto Tangah District Padang City - Rona Taula Sari*; Siska Angreni; Yulfia Nora; Diva Sahaya Arfah (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Children's behavior can be changed by building awareness to keep the environment clean and healthy. To determine the level of knowledge and understanding of elementary school students regarding waste management in the final disposal site (FDS) area, it is necessary to conduct this research with the aim of determining the level of knowledge and understanding of elementary school students regarding waste management in the FDS area. This research uses a quantitative descriptive approach with a survey method. The population of this study was 75 students of class V SDN 30 Aie Dingin. The sampling technique used is total sampling. Data collection uses valid and reliable test instruments. Data were analyzed by descriptive quantitative. Based on the research results, it was obtained that elementary school students' knowledge and understanding of waste management in the Aie Dingin area of Balai Gadang, Koto Tangah District, was in the medium category with a value of 46%, where the level of student knowledge about waste was 66% and the level of understanding of waste management was 54%. It can be said that the knowledge and understanding of fifth grade elementary school students regarding waste management is still low